Tip II sialidoz: Bir vaka takdimi - Kilic, Mustafa; Yildiz, Deniz; Özdemir, Osman; Kocak, Mesut; Günbey, Sacit; Do?an, Yasar; Kilic, Esra (My University, 2013)
Sialidosis is a lysosomal storage disease caused by deficiency of alpha-N-acetyl neuraminidase-1. Sialidosis is classified into two main clinical variants: Type I, the milder form of the disease, and Type II, which can in turn be subdivided into three forms as congenital, infantile or juvenile. We report herein the clinical and biochemical characteristics of one infant with the congenital form of Type II sialidosis. Edema is the distinctive clinical sign in the congenital form of Type II sialidosis among the other lysosomal storage diseases that are on the list of differential diagnoses.
Keywords: Coarse facies; Edema; Sialidosis